The analysis of factors influencing tourists’ choice of green hotels - Zdravković, Stefan; Peković, Jelena (Hotel and Tourism Management, 2020)
In addition to achieving economic goals, tourism companies must take care of social goals and the impact of their business activities on the environment. Social responsibility and economic profit are not contradictory, but rather complementary. Many companies implement Environmental Management System (EMS) in their business operations. Nowadays, Corporate Social Responsibility (CSR) is more and more represented in tourism and hotel industry. An increasing number of tourists are showing concern for the environment and they are staying in green hotels during their travels. The survey was conducted to determine whether the tourist’s intention to stay at the green hotel is affected the tourists’ care for the environment and the perceived value of the green hotel offers. Statistical analysis was performed on a sample of 155 respondents from the territory of the Republic of Serbia. The results of empirical research have shown that these variables have a positive impact on the choice of green hotels, so the study offers important practical implications for tourism and hospitality companies.